Formulasi Sediaan Gel Antiacne Ekstrak Daun Sirih (Piper betle L.) Sebagai Alternatif Terapi Acne Vulgaris Terhadap Bakteri Propionibacterium Acnes Secara In Vitro - Putri Atika Julianti; Titi Agni Hutahaen; Nawafila Februyani (Indonesian Journal of Health Science, 2023)
Betel (Piper betle L.) is one of the plants that has the potential to be developed as a traditional medicine where its existence in Indonesia is abundant, grows independent of the season and is easily found. Preliminary research on phytochemicals from betel leaf shows the content of flavonoid and phenolic compounds and their derivatives, terpenoids, steroids, saponins, tannins, alkaloids and essential oils that can work as antibacterials. The purpose of this study was to formulate betel leaf extract as a gel that meets the requirements in evaluating the physical stability of the preparation as well as knowing the antibacterial activity against Propionibacterium acnes. The research method is true experimental laboratory. The results showed that betel leaf extract concentration of 20% can be formulated into gel preparations with different concentrations of carbopol gel base (0.5%, 1% and 2%) that meet the requirements in the evaluation of physical quality stability of preparations for organoleptic test parameters, homogeneity test, pH test, adhesion test and dispersion test. However, in the adhesion test only F III (2%) meets the standard requirements. Betel leaf extract gel has antibacterial activity against Propionibacterium acnes. The best resistance is found in F I (0.5%) with an average of 10.0 mm, then F II (1%) with an average of 8.5 mm and F III (2%) with an average of 7.3 mm. Sirih (Piper betle L.) merupakan salah satu tanaman yang berpotensi untuk dikembangkan sebagai obat tradisional yang dimana keberadaanya di Indonesia berlimpah, tumbuh tidak tergantung pada musim dan mudah dijumpai. Riset pendahuluan fitokimia dari daun sirih menunjukkan adanya kandungan senyawa flavonoid dan fenolik beserta turunannya, terpenoid, steroid, saponin, tanin, alkaloid dan minyak atsiri yang dapat bekerja sebagai antibakteri. Tujuan penelitian ini adalah untuk memformulasikan ekstrak daun sirih sebagai gel yang memenuhi persyaratan dalam evaluasi stabilitas fisik sediaan serta mengetahui aktivitas antibakteri terhadap Propionibacterium acnes. Metode penelitian adalah true experimental laboratory. Hasil penelitian menunjukkan ekstrak daun sirih konsentrasi 20 % dapat diformulasikan ke dalam sediaan gel dengan konsentrasi basis gel carbopol yang berbeda (0,5 %, 1 % dan 2 %) yang memenuhi persyaratan dalam evaluasi stabilitas mutu fisik sediaan untuk parameter uji organoleptik, uji homogenitas, uji pH, uji daya lekat dan uji daya sebar. Namun, pada uji daya lekat hanya F III (2 %) yang memenuhi standar persyaratan. Gel ekstrak daun sirih memiliki aktivitas antibakteri terhadap Propionibacterium acnes. Daya hambat terbaik terdapat pada F I (0,5 %) dengan rerata 10,0 mm, kemudian F II (1 %) dengan rerata 8,5 mm dan F III (2 %) dengan rerata 7,3 mm.